1999
DOI: 10.1007/s004970050189
|View full text |Cite
|
Sign up to set email alerts
|

Pollen sporopollenin: degradation and structural elucidation

Abstract: We report the isolation of purified sporopollenin from pollen grains of different species and its complete solubilization. Exine from Pinus pinaster, Betula alba, Ambrosia elatior and Capsicum annuum was extracted by treatment with hydrogen fluoride in pyridine. These exines were purified from their aromatic moieties and from fatty acids linked by ester bonds using acidolysis and saponification treatments. The biopolymer obtained retains almost completely the shape of the original pollen grain. Fourier-transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
120
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 23 publications
12
120
0
2
Order By: Relevance
“…The H-to-C and O-to-C atomic ratios of NHC (e.g., sporopollenin) are lower in this study than those reported previously. 37 It seems that there are significant correlations among H-to-C and O-to-C atomic ratios and the sorption affinity of Phen by the pollens and their fractions, as observed previously for other biosorbents. 20 Structure of Bulk Pollen and Isolated Fractions.…”
Section: ■ Materials and Methodssupporting
confidence: 70%
“…The H-to-C and O-to-C atomic ratios of NHC (e.g., sporopollenin) are lower in this study than those reported previously. 37 It seems that there are significant correlations among H-to-C and O-to-C atomic ratios and the sorption affinity of Phen by the pollens and their fractions, as observed previously for other biosorbents. 20 Structure of Bulk Pollen and Isolated Fractions.…”
Section: ■ Materials and Methodssupporting
confidence: 70%
“…lap3-2 leads to a wide variety of metabolic consequences in developing anthers. Given the model of sporopollenin composed of fatty acid and phenolic compounds (Guilford et al 1988;Kawase and Takahashi 1995;Ahlers et al 1999Ahlers et al , 2000Ahlers et al , 2003Dominguez et al 1999;MeuterGerhards et al 1999;Bubert et al 2002), it is of interest to note that some changes were detected in the levels of lipids (such as a-linolenic acid, 1-18:3-lysophophatidylethanolamine, 1-16:0-lysophophatidylethanolamine, a-eleosteric acid, and 10E,12Z-octadecadienoic acid, linoleic acid, nonacosane and palmitic acid) and of at least one phenylpropanoid (naringenin chalcone).…”
Section: Lap3 Is Likely Not a Strictosidine Synthasementioning
confidence: 99%
“…In addition, a possibility exists that sporopollenin is not a single substance, but instead varies chemically between species and even between different stages of development (Hemsley et al 1993;Meutergerhards et al 1995). Despite these difficulties, tracer experiments, NMR and spectroscopic/spectrometric studies have yielded a model of sporopollenin composed of polyhydroxylated unbranched aliphatics and phenolics covalently coupled with ether and ester linkages (Guilford et al 1988;Kawase and Takahashi 1995;Ahlers et al 1999Ahlers et al , 2000Ahlers et al , 2003Dominguez et al 1999;Meuter-Gerhards et al 1999;Bubert et al 2002).…”
mentioning
confidence: 99%
“…The exine, composed of a substance called sporopollenin, is highly crosslinked and consists of fatty acid, phenylpropanoid, and phenolic substances. Sporopollenin is an extraordinarily stable natural organic substance [18,19]. The monomers and macromers thought to comprise sporopollenin include aliphatic chains, aromatic cross-linkers (mainly cinnamic acids), ether cross-linkers, Electronic supplementary material The online version of this article (https://doi.org/10.1007/s42247-018-0009-x) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%